The Effectiveness of Forward Leaning Position and Pursed Lip Breathing on Dyspnea in Patients with Lung Disease - Astuti, Widia; Sitorus, Ratna; Herawati, Tuti; Aryani, Denissa Faradita; Pratiwi, Tiara Zakiyah; Maemun, Siti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Dyspnoea is the most common and distressing symptom of lung disease, and it causes uncomfortable feelings. Dyspnoea occurs in patients with lung diseases such as lung cancer, COPD, asthma and tuberculosis. Positioning that can reduce shortness of breath in COPD patients is the tripod position and breathing exercises, namely lip breathing exercises, which can affect oxygen saturation. The aim of study is to determine the effectiveness of the application of forward leaning position and pursed lip breathing on dypsnea in patients with lung disease. Pursed lips breathing exercises and a tripod position significantly improved symptoms of shortness of breath and strengthened respiratory muscles. To determine the effectiveness of applying the forward leaning position and pursed lip breathing for dyspnea in patients with lung disease. This research is quantitative with a quasi-experimental design with a pretest-posttest design approach without a control group design. The inclusion criteria for adult patients ≥ 18 years, patients with lung disease: COPD, Asthma, Tuberculosis and Lung Cancer and moderate to severe dyspnea at rest as measured by the Modified Borg Dyspnea Scale (MBDS ≥3). The number of samples was 30 people. The results of the analysis using the Wilcoxon Test and the results obtained were that providing a forward leaning position (FLP) and Pursed Lips Breathing (PLB) breathing exercises in patients with lung disease could significantly reduce the degree of dyspnea. The application of a combination of forward-leaning positions and pursed lips breathing exercises can have an effect on reducing the degree of dyspnea in patients.